Analisis Brand Image terhadap Minat Mahasiswa Masuk Perguruan Tinggi menggunakan Metode Cochrand Q Test dan Marketing Mix (Studi Kasus: Mahasiswa S-1 Teknik Industri UIN Suska Riau) - Tiyandari, Reni Sulis; Kusumanto, Ismu; Suherman, Suherman; Umam, Muhammad Isnaini Hadiyul; Nofirza, Nofirza (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This study aims to analyze the factors that shape the brand image of the Industrial Engineering Department of UIN Suska Riau and design a promotional strategy using the Cochran test and marketing mix methods. Data were obtained from 100 respondents through a questionnaire. The results showed significant differences between the attributes tested, with a Q value > X² table in all tests. The main factors that shape the brand image include reputation, accreditation, teaching staff, quality of education, and student comfort.